Hubungan Health Locus of Control dengan Kepatuhan Diet pada Pasien Diabetes Mellitus Tipe 2 di RSUD Kota Depok Tahun 2020 - Adhanty, Shania; Ayubi, Dian; Anshari, Dien (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2021)
Background. Diabetes Mellitus (DM) caused 4.2 million deaths in 2019. In Indonesia, DM is an NCD that causes major deaths. Dietary adherence becomes a vital behavior and requires self-control. Objective. This study aimed to determine the relationship between health locus of control on internal, powerful-others, chance dimensions and other factors with dietary adherence among type 2 DM patients at Depok City Hospital in 2020. Method. This study used a cross-sectional design and data collection through convenience sampling on 52 type 2 DM patients who visited internist poly in Depok City Hospital. Results. This study indicates that patients have adequate dietary adherence values 66,23 on a scale of 100. Pearson correlation test results show a significant relationship between health locus of control on internal and powerful-others dimensions with a moderate and positive relationship with dietary adherence (r= 0,46 and r= 0,28). Meanwhile, the chance dimension shows a moderate and negative relationship with dietary adherence (r= -0,28). Conclusion: There is a significant relationship between health locus of control internal, powerful others and chance dimensions with dietary compliance with moderate strength. The direction of the correlation is positive on the internal dimension and powerful others while negative on the chance dimension.